2018
DOI: 10.1002/jsid.624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disparity and viewing ambient illumination on stereoscopic viewing: An eye movement approach

Abstract: Researchers have found that factors related to viewing content and viewing environment could influence viewers' stereoscopic viewing experiences. In this paper, the effect of both disparity and viewing ambient illumination condition on stereoscopic viewing was investigated by using an eye movement approach. The eye movement responses to random dot stereograms (RDS) stimuli in stereoscopic viewing were studied by performing a fusion range measurement experiment involving a judgment task. The fusion ranges under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In our previous experiment, low illumination conditions (120 and 15 lux) has been studied, and results showed that the 3D fusion range has no significant difference when the illuminance is no more than 120 lux. 16 According to the China illumination standards GB 50034-2013, the desired illuminance in indoor environment is 100 to 500 lux. 25 In order to avoid the selected illuminance levels to be in the same range, the high (500 lux) and low illuminance (100 lux) conditions were set up, and the luminance of 3D display (5 lux) and other measurement devices can be negligible in the experiment.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous experiment, low illumination conditions (120 and 15 lux) has been studied, and results showed that the 3D fusion range has no significant difference when the illuminance is no more than 120 lux. 16 According to the China illumination standards GB 50034-2013, the desired illuminance in indoor environment is 100 to 500 lux. 25 In order to avoid the selected illuminance levels to be in the same range, the high (500 lux) and low illuminance (100 lux) conditions were set up, and the luminance of 3D display (5 lux) and other measurement devices can be negligible in the experiment.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
“…15 Our earlier study explored the fusion ranges under two ambient illumination conditions (120 lux and 15 lux), and the results demonstrated that there was no significant difference between two ambient illumination conditions in both crossed disparity and uncrossed disparity aspects. 16 However, the insignificant results may be related to the selected levels of ambient illumination, which are in low illumination range.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is currently no simple and stable coefficient to measure or predict the degree of interest in a digital learning area. Though there are many studies on eye movement and degree of interest [16], the behaviors change with the viewing environment, which means that we cannot simply consider every viewing behavior as being directly comparable.…”
Section: Introductionmentioning
confidence: 99%